Online micro-solid-phase extraction based on boronate affinity monolithic column coupled with high-performance liquid chromatography for the determination of monoamine neurotransmitters in human urine - Yang, Xiaoting; Hu, Yufei; Li, Gongke (Journal of Chromatography A, 2014)
•A boronate affinity monolithic column was prepared by in situ polymerization.•The monolithic column showed high extraction capacity to four monoamines.•An online micro-solid-phase extraction coupled with HPLC method was developed.•The method was successfully applied to online analysis of monoamines in human urine. Quantification of monoamine neurotransmitters is very important in diagnosing and monitoring of patients with neurological disorders. We developed an online analytical method to selectively determine urinary monoamine neurotransmitters, which coupled the boronate affinity monolithic column micro-solid-phase extraction with high-performance liquid chromatography (HPLC). The boronate affinity monolithic column was prepared by in situ polymerization of vinylphenylboronic acid (VPBA) and N,N′-methylenebisacrylamide (MBAA) in a stainless capillary column. The prepared monolithic column showed good permeability, high extraction selectivity and capacity. The column-to-column reproducibility was satisfactory and the enrichment factors were 17–243 for four monoamine neurotransmitters. Parameters that influence the online extraction efficiency, including pH of sample solution, flow rate of extraction and desorption, extraction volume and desorption volume were investigated. Under the optimized conditions, the developed method exhibited low limit of detection (0.06–0.80μg/L), good linearity (with R2 between 0.9979 and 0.9993). The recoveries in urine samples were 81.0–105.5% for four monoamine neurotransmitters with intra- and inter-day RSDs of 2.1–8.2% and 3.7–10.6%, respectively. The online analytical method was sensitive, accurate, selective, reliable and applicable to analysis of trace monoamine neurotransmitters in human urine sample.